Association Between Uric Acid Levels and Metabolic Risk Factors in Overweight and Obese Children - Shazia Bahar, Muhammad Zubair Faiz, Ahmad Tariq, Abdur Rauf Hammad, Renad Al Mefleh, Muhammad Azhar Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Childhood overweight and obesity are increasing rapidly in Pakistan and are strongly associated with early metabolic disturbances. Uric acid, once considered an inert metabolic by-product, is now recognized as a potential biomarker linked to insulin resistance, lipid abnormalities, and elevated blood pressure. This study aims to evaluate the association between serum uric acid levels and major metabolic risk factors among overweight and obese children. Methods: This cross-sectional study was conducted at Khyber Teaching Hospital, Peshawar, and the Punjab Institute of Cardiology, Lahore, from October 2022 to July 2023. A total of 100 overweight and obese children aged 6–17 years were enrolled using consecutive sampling. Anthropometric measurements, blood pressure, and fasting biochemical parameters serum uric acid, glucose, insulin, and lipid profile were obtained. Insulin resistance was calculated using the HOMA-IR formula. Participants were categorized into uric acid tertiles, and metabolic parameters were compared across groups. Statistical analysis included ANOVA, Pearson correlation, and multivariable linear regression. Results: Higher uric acid levels were significantly associated with increased fasting insulin (p < 0.001), higher HOMA-IR (p < 0.001), elevated triglycerides (p < 0.001), higher LDL-cholesterol (p < 0.01), lower HDL-cholesterol (p = 0.02), and increased systolic blood pressure (p < 0.01). Uric acid showed moderate positive correlations with BMI percentile, fasting insulin, HOMA-IR, triglycerides, and systolic blood pressure. Regression analysis confirmed uric acid as an independent predictor of insulin resistance after adjusting for confounders (β = 0.35, p = 0.002). Conclusion: Elevated serum uric acid is strongly associated with multiple metabolic risk factors among overweight and obese children. Routine assessment of uric acid may serve as a simple, cost-effective tool for early identification of high-risk pediatric groups requiring metabolic monitoring and intervention. Keywords: Uric acid, Childhood obesity, Insulin resistance, Metabolic syndrome, Pediatric dyslipidemia.